2016
DOI: 10.1253/circj.cj-16-0326
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic Polymorphic Ventricular Tachycardia

Abstract: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is an inherited cardiac arrhythmia disorder that is characterized by emotion-and exercise-induced polymorphic ventricular arrhythmias and may lead to sudden cardiac death (SCD). CPVT plays an important role in SCD in the young and therefore recognition and adequate treatment of the disease are of vital importance. In the past years tremendous improvements have been made in the diagnostic methods and treatment of the disease. In this review, we summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 70 publications
1
71
0
1
Order By: Relevance
“…CPVT is a rare disease with an estimated prevalence of 1:10,000 [159,160]. CPVT commonly manifests at an early age and has poor spontaneous outcome [161].…”
Section: Catecholaminergic Polymorphic Ventricular Tachycardiamentioning
confidence: 99%
“…CPVT is a rare disease with an estimated prevalence of 1:10,000 [159,160]. CPVT commonly manifests at an early age and has poor spontaneous outcome [161].…”
Section: Catecholaminergic Polymorphic Ventricular Tachycardiamentioning
confidence: 99%
“…Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a rare (prevalence: 1/10,000) channelopathy characterized by premature ventricular contractions (PVCs), and monomorphic, bidirectional, or polymorphic ventricular tachycardia (VT). Arrhythmias are often triggered by exercise, acute emotion, or stress and most patients with CPVT have structurally normal hearts and normal resting electrocardiograms (ECG) . In addition to VT, atrial arrhythmias such as atrial fibrillation (AF), atrial flutter, and atrial abnormalities such as sinus node dysfunction and atrial standstill have been reported .…”
Section: Introductionmentioning
confidence: 99%
“…Variants in cardiac ryanodine receptor ( RYR2 ) and calsequestrin 2 ( CASQ2 ) are most common, contributing to ~60% and 5% of CPVT cases, respectively. 6 Additional genes, including Calmodulin 1( CALM1 ) and Triadin ( TRDN ), are also associated with CPVT. 6 At the molecular level, CPVT is commonly associated with aberrant sarcoplasmic reticulum calcium release through RyR2.…”
mentioning
confidence: 99%
“…6 Additional genes, including Calmodulin 1( CALM1 ) and Triadin ( TRDN ), are also associated with CPVT. 6 At the molecular level, CPVT is commonly associated with aberrant sarcoplasmic reticulum calcium release through RyR2. 6 Incomplete penetrance, diverse inheritance patterns, and phenocopy of other cardiac arrhythmia syndromes complicate the genetic understanding of disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation